Implementasi Miniatur Kapal Menggunakan Dinamo Tamia - Aliefian Hendra Wardana; Fiza Trisna Aqilla; Kurniadi Mizan Sidiq; Umar Said Fathullah; Rudi Susanto (Prosiding Seminar Nasional Teknologi Informasi dan Bisnis, 2023)
In addition, this abstract will highlight the application of renewable energy technology in wooden crane boats. The use of solar panels and solar-powered energy storage systems helps reduce ship dependence on fossil fuels, as well as maintain the balance ofcoastal ecosystems. Local wisdom remains the cornerstone in the development of wooden crane boats that incorporate electronic technology. At the same time, this technological adaptation enriches local wisdom values by increasing the efficiency, safety and sustainability of ships. In conclusion, the use and development of wooden otok-otok ships with a touch of electronics is an evolution of local wisdom in the field of shipping. The integration of electronic technologies such as navigation sensors, communications and renewable energy helps improve the performance and efficiency of this ship. Maintaining local wisdom values while adopting technological innovations is the key in maintaining the sustainability of the otok-otok kayu in the modern era which is increasingly connected electronically.